Fetomaternal outcome in patients with early preterm labour following administration of magnesium sulphate - a hospital based prospective study - Robin Medhi; Indira Das; Rumen Ch Boro; Wahida Naznin (Barpeta Obstetrics and Gynaecological Society, 2023)
Objective: To assess the effectiveness of magnesium sulfate as a neuroprotective agent in early preterm labour (28 to 32 weeks). To assess any maternal or fetal adverse effects after giving magnesium sulfate. Methods: Hospital based prospective observational study. Initially 72 pregnant women with preterm labour, planned preterm birth due to maternal or fetal indication between 28 to 32 weeks of gestation were selected. Among them 37 women received MgSO4, out of which 2 women could not be followed up. So, the study was conducted between 35 women as study group (Group A), who received MgSO4 and 35 women as control group (Group B), who did not receive MgSO4. Corticosteroid was given to both groups. Results: The number of babies who developed IVH in the non-MgSO4 group was significantly greater (5/35, 14.3 %) than in the MgSO4 group (3/35, 8.6%) (p Value = 0.452). In this study 3 (8.6%) ELBW babies in nonMgSO4 group had IVH compared to 2 (5.7%) in MgSO4 group. 2 (5.7%) VLBW babies in nonMgSO4 group had IVH while 1 (2.9%) VLBW babies in MgSO4 group had IVH. According to the gestational age in nonMgSO4 group 20% (7/35) of the babies between 28 to 30 weeks required intubation compared to 11.4% (4/35) babies in MgSO4 group. 14.3% (5/35) of the babies between 30 to 32 weeks in nonMgSO4 group required intubation where only 5.7% (2/35) babies in MgSO4 group required intubation. (p Value = 0.017). 5.7% (2/35) babies between 30 to 32 weeks of gestation in nonMgSO4 group had delayed milestones, while no baby showed delayed milestones in MgSO4group. Conclusions: Antenatal MgSO4 appears to minimize the likelihood of invasive mechanical ventilation, the need for continuing respiratory support, intraventricular hemorrhage. Antenatal MgSO4 has similar effects across a range of preterm gestational ages.